Nanomaterials for cascade promoted catalytic cancer therapy. Issue 6 (18th May 2021) - Tong, Zongrui; Gao, Yong; Yang, Huang; Wang, Weilin; Mao, Zhengwei
Abstract: Catalytic therapy utilizing special substances (e.g., hydrogen peroxide and glucose) in tumor sites has attracted wide interest to achieve tumor‐specific therapy or improve the efficacy of other treatments. Benefiting from the selectivity and high activity of catalytic chemistry, efficient cancer therapy is available with negligible side effects. Numerous works, which are focused on further augmenting catalytic therapy with cascade strategies, have been reported with biocompatible nanomaterials composed of natural enzymes and/or nanozymes. Herein, we summarized catalytic reactions and nanomaterials in cascade strategy‐involved cancer therapy. With rapid advances in chemistry and nanomaterials, developing more selective and efficient cascade catalytic strategies will continue to be promising and challenging for cancer therapy. Abstract :